RESONANCE OF WATER WAVES - FIRNALISY ARIYANA (NIM : 10108089); Pembimbing : Dr. Sri Redjeki Pudjaprasetya, NADA
Every system that has a capability to vibrate (including water) must have a natural frequency. When a driving force applied to a system has frequency equals to the natural frequency of the system, resonance will occur. Resonance can be identified by a dramatic increase in amplitude of the resultant vibrations. In this thesis we discuss resonance in water basin. The natural frequency of a basin can be obtained from the linear shallow water equation with suitable basin conditions. The numerical scheme used to solve this linear shallow water equation is the conservative finite volume scheme based on a staggered grid. Using this non dissipative scheme, we are able to simulate perfect resonances in closed basin and in semi closed basin. We also simulate resonance in a basin with layers of water with two densities: upper layer is water with smaller density.